Implementasi Psikoedukasi Untuk Meningkatkan Pengetahuan Perilaku Seksual Sehat Pada Siswa Sma Negeri 1 Pandaan - zam roni; sinta wati; rizki intan; Dwi Pusparini (Universitas Darul Ulum, 2024)
Adolescents are a vulnerable group to external influences, particularly sexual behavior influences. They still struggle to understand healthy sexual behavior. The purpose of this service is to carry out psychoeducation as a method of seminar that broadens the understanding of healthy sexual behavior for students in SMA Negeri 1 Pandaan. The methods applied in this activity are lecturing, ice breaking, and training. Implementation technique in this service includes the planning stage, the implementation stage, and the evaluation stage. This service activity showed results that the students know well about the importance of healthy sexual behavior. Moreover, the chosen healthy relationship ambassador can influence others by giving knowledge about healthy sexual behavior. Keywords: psychoeducation, healthy sexual behavior, youth reproductive health